2021
DOI: 10.54203/scil.2021.wvj84
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Replacing Soybean Meal with Sunflower Meal, Sesame Meal, and Black Seed Meal in diets of Barki Lambs

Abstract: Crude protein content in animal diet is considered the first important factor for nutritionists when they start to formulate a diet for different types of animals. Therefore, this experiment was conducted to investigate the effect of substituting soybean seed meal by different protein sources on lamb’s diet in terms of nutrients digestibility, and growth performance. Therefore, four tested concentrate feed mixtures (CFM, 14% crude protein) were designed. The CFM1 contained soybean meal as the only source of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Treatments did not affect nutrient digestibility. Consistent with the present results, El-Tanany et al [4] and Cherif et al [11] observed unchanged apparent digestibility of DM, OM, CP, and NDF when feeding N. sativa seeds to lambs. Many other experiments showed that replacing protein feed in the diet with NSM or the administration of NSM directly as a feed additive improved nutrient digestibility or at least CP digestibility [5,33,41].…”
Section: Diets Digestibility and Nutritive Valuesupporting
confidence: 92%
See 3 more Smart Citations
“…Treatments did not affect nutrient digestibility. Consistent with the present results, El-Tanany et al [4] and Cherif et al [11] observed unchanged apparent digestibility of DM, OM, CP, and NDF when feeding N. sativa seeds to lambs. Many other experiments showed that replacing protein feed in the diet with NSM or the administration of NSM directly as a feed additive improved nutrient digestibility or at least CP digestibility [5,33,41].…”
Section: Diets Digestibility and Nutritive Valuesupporting
confidence: 92%
“…The minimal effects of treatments on nutrient digestibility were reflected as unaffected diet nutritive value. Similar results on TDN and DCP were observed by El-Tanany et al [4].…”
Section: Diets Digestibility and Nutritive Valuesupporting
confidence: 90%
See 2 more Smart Citations